The Difference in the Influence of Problem-Focused and Emotion-Focused Coping on Student Academic Stress in the VUCA Environment in Malang City - Kartikasari, Dhian; Dennada Bagus Putra Perdana (EDUTEC : Journal of Education And Technology, 2025)
The VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era has intensified academic pressure in higher education, particularly among first-year health students. This study examined differences in the effects of problem-focused coping and emotion-focused coping on academic stress. Using a cross-sectional quantitative design, 210 first-year health students in Malang City were selected through proportional random sampling. Data were collected using validated and reliable Likert-scale questionnaires. Results indicated that academic stress levels were moderate to high (mean = 61.84; SD = 10.72). Problem-focused coping showed a higher mean compared to emotion-focused coping. Correlation analysis revealed that problem-focused coping was significantly negatively associated with academic stress (r = −0.41; p < 0.001), while emotion-focused coping showed a significant positive association (r = 0.36; p < 0.001). Multiple linear regression analysis demonstrated a significant model (F = 38.72; p < 0.001), explaining 27.4% of the variance (R² = 0.274). Partially, problem-focused coping had a stronger negative effect (β = −0.38), whereas emotion-focused coping had a positive effect (β = 0.29). These findings indicate that problem-focused coping is more effective in reducing academic stress, while emotion-focused coping tends to provide only short-term relief and may be maladaptive if dominated by avoidance strategies.